GE_GERICHTE C/19087/2012 vom 27. November 2012 - GE Cour de justice (2012)
PROTECTION DE L'UNION CONJUGALE; DROIT DE GARDE; VISITE; RELATIONS PERSONNELLES; OBLIGATION D'ENTRETIEN; DÉBUT | CC.176.3; CC.273; CC.163; CC.255